Impaired Hippocampal Glutamate and Glutamine Metabolism in the db/db Mouse Model of Type 2 Diabetes Mellitus - Jens Velde Andersen; Jakob Dahl Nissen; Sofie Kjellerup Christensen; Kia Hjulmand Markussen; Helle Sønderby Waagepetersen (Neural Plasticity)
Type 2 diabetes mellitus (T2DM) is a risk factor for the development of Alzheimer’s disease, and changes in brain energy metabolism have been suggested as a causative mechanism. The aim of this study was to investigate the cerebral metabolism of the important amino acids glutamate and glutamine in the db/db mouse model of T2DM. Glutamate and glutamine are both substrates for mitochondrial oxidation, and oxygen consumption was assessed in isolated brain mitochondria by Seahorse XFe96 analysis. In addition, acutely isolated cerebral cortical and hippocampal slices were incubated with [U-13C]glutamate and [U-13C]glutamine, and tissue extracts were analyzed by gas chromatography-mass spectrometry. The oxygen consumption rate using glutamate and glutamine as substrates was not different in isolated cerebral mitochondria of db/db mice compared to controls. Hippocampal slices of db/db mice exhibited significantly reduced 13C labeling in glutamate, glutamine, GABA, citrate, and aspartate from metabolism of [U-13C]glutamate. Additionally, reduced 13C labeling were observed in GABA, citrate, and aspartate from [U-13C]glutamine metabolism in hippocampal slices of db/db mice when compared to controls. None of these changes were observed in cerebral cortical slices. The results suggest specific hippocampal impairments in glutamate and glutamine metabolism, without affecting mitochondrial oxidation of these substrates, in the db/db mouse.